(3UhJ GdLRGFQ (B:s (3TYQ (B/s - (3HhRjOj, eMeOs ((3GdLRGFQ (B:s (3GdecJHI GdhWfjI GdLRGFQjI ,s, 1997)
(3jYJHQ gPG GdOjhGf eSGgeI ef GdecJHI HhVY dHfI aj UQM JGQjN QLGd fhaeHQ h gOjI JVe HGbI ef GdGTYGQ ddCWaGd aj ONhdge GdeOQSj h ddcHGQ djhGUd dLejY fbd GdQSGdI h jQOOhG cdeGJ GdGOjH GdeLGgO h GdTGYQ GdafGf MJi dG JehJ GdcdeI GdWjHI aj GdHdO GdWjHs
Keywords: (3TYQs; (3GdLRGFQs